2005
DOI: 10.1016/j.otohns.2005.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Acute Sinusitis in Children

Abstract: Despite significant deficits on presentation, permanent morbidity was low. Streptococcus milleri is a common pathogen with complications of sinusitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(70 citation statements)
references
References 23 publications
5
63
1
1
Order By: Relevance
“…In accordance with literature findings [6], our cases of acute bacterial rhinosinusitis that proved resistant to conservative treatment and complications secondary to acute sinusitis were admitted most frequently in the period from January to March (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…In accordance with literature findings [6], our cases of acute bacterial rhinosinusitis that proved resistant to conservative treatment and complications secondary to acute sinusitis were admitted most frequently in the period from January to March (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…Jain and Rubin [10] also believe that cellulitis is more prevalent during winter months, corresponding with higher prevalence of sinusitis on these cold days. Other authors have reported that orbital and PC are seen more in the cold months of late fall to early spring, compatible with the peak of upper respiratory viral infections [11]. The higher prevalence of cellulitis in spring in our series may be related to the higher occurrences of allergies and aggravation of the background sinusitis in this season.…”
Section: Discussionsupporting
confidence: 78%
“…While most patients recover uneventfully, serious orbital or intracranial complications may occur. When complications of acute sinusitis arise, they involve the orbit in the majority of children, reported in 91% of pediatric patients in a recent series [2] and usually are secondary to acute ethmoid sinusitis [3]. A classification of orbital complications of sinusitis was described by Chandler in 1970 (Table 1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Complications may result from osteitic bone destruction, congenital or acquired bony defects, or via thrombophlebitis of communicating veins and have the potential to result in serious complications such as blindness and death [5,6]. While medical treatment of pediatric orbital cellulitis results in excellent outcomes [2], surgical drainage has traditionally been recommended for SPOA secondary to sinusitis [3,7]. Surgical options include traditional external approaches to the orbit, and more cosmetically appealing procedures including the transcaruncular external approach [8] and endoscopic drainage [9,10].…”
Section: Introductionmentioning
confidence: 99%